The Role of Monetary Authorities and Banking Regulators in Supporting Sharia Bank Liquidity - Restika, Restika; Puteri, Hesi Eka (LP2M IAIN Palopo, 2023)
This study aims to analyze the influence of the role of monetary authorities and banking regulators on the liquidity of Islamic banks in Indonesia. This research uses a qualitative approach with panel data analysis method. The sample of this study is 27 Islamic banks operating in Indonesia during the period 2019-2022. The data used are secondary data obtained from Islamic bank financial statements, Islamic banking statistics, and publications of relevant authorities. The results of this study show that the role of monetary authorities and banking regulators has a positive and significant influence on the liquidity of Islamic banks in Indonesia. This shows that the role of monetary authorities and banking regulators is very important in influencing the performance, growth, and stability of Islamic banking in Indonesia. This research provides theoretical and practical contributions for academics, practitioners, and policy makers with an interest in the liquidity management of Islamic banks. This research also provides input and advice for monetary authorities and banking regulators in increasing their role in supporting Islamic bank liquidity in Indonesia.